Peachtree Borers in the Home and Commercial Peach Orchard - Russell F. Mizell, III (EDIS)
The peachtree borer, Synanthedon exitiosa (Say), and the lesser peachtree borer, S. pictipes (Grote and Robinson), are the most important pests of peach in the southern United States. The larvae of these day-flying moths mine beneath the bark of the trunk and scaffold limbs of peach trees of all ages. Feeding damage by these larvae weakens trees and decreases productivity. If there is complete girdling of the trees by the larvae, tree death can occur. This document is ENY-691 (formerly ENT-57), one of a series of the Department of Entomology and Nematology, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published: December 1985. Revised: November 2003.